2009
DOI: 10.5009/gnl.2009.3.3.174
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Small-Intestinal Bacterial Overgrowth and Intestinal Permeability in Patients with Irritable Bowel Syndrome

Abstract: Background/AimsSmall-intestinal bacterial overgrowth (SIBO) is a frequent finding in patients with irritable bowel syndrome (IBS). Many patients with IBS also have abnormal intestinal permeability, which is probably due to low-grade inflammation in the intestinal mucosa. Our aim was to verify the relationship between SIBO and small-intestinal permeability in IBS patients.MethodsA cohort of 38 IBS patients (20 women and 18 men; age range 16-70 years; mean age 40.2 years) with symptoms that fulfilled Rome-II cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 34 publications
0
32
0
1
Order By: Relevance
“…Studies using the urine excretion of 50 Cr-EDTA taken with a 200 kcal nutrient test meal showed elevations in both 0-6 h and 6-24 h urinary collections, which approximate to small and large bowel permeability in both PI-IBS and IBS with constipation (IBS- Dysbiosis in microbial flora resulting in the lack of signals to maintain barrier function Bansal et al, 36 Fukuda et al, 37 Hamer et al 37 Dysbiosis resulting in an increase in signals that break the barrier . 54 Another study using the ratio of PEG 3500-400 urine excretions showed increases in both IBS-D and IBS-C. 55 Using intestinal biopsies placed directly in mini-Ussing chambers, Piche and colleagues 15 demonstrated that the paracellular permeability to FITC sulfonic acid was significantly increased regardless of IBS subtype in a small sample (12 IBS patients). They also showed a reduction in a tight junction protein ZO-1 mRNA, but no difference in occludin.…”
Section: Evidence For Increased Permeability In Ibs Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using the urine excretion of 50 Cr-EDTA taken with a 200 kcal nutrient test meal showed elevations in both 0-6 h and 6-24 h urinary collections, which approximate to small and large bowel permeability in both PI-IBS and IBS with constipation (IBS- Dysbiosis in microbial flora resulting in the lack of signals to maintain barrier function Bansal et al, 36 Fukuda et al, 37 Hamer et al 37 Dysbiosis resulting in an increase in signals that break the barrier . 54 Another study using the ratio of PEG 3500-400 urine excretions showed increases in both IBS-D and IBS-C. 55 Using intestinal biopsies placed directly in mini-Ussing chambers, Piche and colleagues 15 demonstrated that the paracellular permeability to FITC sulfonic acid was significantly increased regardless of IBS subtype in a small sample (12 IBS patients). They also showed a reduction in a tight junction protein ZO-1 mRNA, but no difference in occludin.…”
Section: Evidence For Increased Permeability In Ibs Patientsmentioning
confidence: 99%
“…Studies using the urine excretion of 50 Cr‐EDTA taken with a 200 kcal nutrient test meal showed elevations in both 0–6 h and 6–24 h urinary collections, which approximate to small and large bowel permeability in both PI‐IBS and IBS with constipation (IBS‐C) 54 . Another study using the ratio of PEG 3500–400 urine excretions showed increases in both IBS‐D and IBS‐C 55 . Using intestinal biopsies placed directly in mini‐Ussing chambers, Piche and colleagues 15 demonstrated that the paracellular permeability to FITC sulfonic acid was significantly increased regardless of IBS subtype in a small sample (12 IBS patients).…”
Section: Introductionmentioning
confidence: 98%
“…Another study showed unchanged claudin-1 protein expression in IBS-C as compared to healthy individuals [7]. In vivo measurements of intestinal permeability using urinary excretion of orally ingested, poorly-absorbable saccharides have also shown variable results in IBS-C. One study has shown increased permeability using polyethylene glycol (PEG) 3350/400 [8], another using PEG 400/1500/4000 showed no difference [9] and one using 51 Cr-EDTA showed decreased permeability [10]. Variability in timing of urine collection and dietary contamination often limits interpretation from these in vivo assays.…”
Section: Introductionmentioning
confidence: 99%
“…Increased gut permeability and defects in intestinal barrier function are associated with several functional gastrointestinal disorders such as irritable bowel syndrome (IBS) (1). Studies using urine excretion showed increased intestinal permeability to 50 Cr-EDTA and low molecule polyethylene glycol (PEG-400) in patients with IBS (2, 3). More recently, Rao and his colleagues (4) reported that both small bowel and colon permeability were increased in IBS patients with diarrhea by measuring saccharides lactulose and mannitol secretion in urine collections.…”
Section: Introductionmentioning
confidence: 99%
“…1 Studies using urine excretion showed increased intestinal permeability to 50 Cr-EDTA and low molecule polyethylene glycol (PEG-400) in patients with IBS. 2,3 More recently, Rao et al 4 reported that both small bowel and colon permeability were increased in IBS patients with diarrhea by measuring saccharides lactulose and mannitol secretion in urine collections. Another study using intestinal biopsies in Ussing chambers demonstrated that colonic paracellular permeability to sulfonic acid was significantly increased in IBS patients regardless of IBS subtype.…”
Section: Introductionmentioning
confidence: 99%